Consulting essentials : the art and science of people, facts, and frameworks - Kavanaugh, Jeff (Tantor Media, 2020)
How do you become a world-class consultant'This is the question on the minds of thousands of young consultants as they graduate from the classrooms of the world's business schools to the offices of top consulting firms. Yet, few of them have been formally trained on the concepts that elevate consultants to the top of their field. Drawing on his experience as a senior partner at a multi-billion dollar consulting firm and adjunct professor at the University of Texas at Dallas MBA program, Jeff Kavanaugh is ready to share the tools of the trade for young professionals to quickly scale the consulting learning curve. Pulling together the best content from his own experience, as well as other world-class consulting leaders and industry professionals he has worked with, Kavanaugh has distilled the lessons into the key skills that separate the best from the rest.